ANALISIS PERBEDAAN ASUPAN ZAT GIZI BERDASARKAN STATUS GIZI WANITA DEWASA PESERTA MAJLIS TAKLIM NURUL HIDAYAH CIPULIR KEBAYORAN LAMA JAKARTA SELATAN - Ronitawati, Putri; Elvandari, Miliyantri (Jurnal Nutrire Diaita (Ilmu Gizi), 2017)
Food and nutrition are related because the nutritional status of an individual is influenced by the food consumed. A balanced nutritional intake is required to achieve optimal health and prevention of non-communicable diseases. In adulthood the age will change many changes both physical changes and changes in psychology and social. Riskesdas 2010 results show that 21.7% of Indonesian adults are overweight (including obese), and women have a higher prevalence (26.9%) than males (16.3%) (Balitbangkes 2010). The purpose of this research is to analyze the difference of nutrient intake based on nutritional status of adult woman. The type of this study was observational with cross sectional study design with total subjects of 33 people (total sampling). Analysis with independent t-test showed that there were significant differences in protein intake (p Value 0.043) and vitamin B1 intake (p Value 0.049) based on nutritional status of respondents. Intake of nutrients need to be adjusted with balanced nutrition so that the need for nutritional education gradually so as to meet the adequacy of nutrients.Â Keywords: nutritional intake, nutritional status, adult women